Learning English for Specific Purposes Using Artificial Intelligence: University Students’ Perspectives - Dang Ngoc Quang; Dao Bui Dieu Minh; Ta Thi Thanh Hien (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This article explores the effectiveness of artificial intelligence (AI) in learning English for Specific Purposes (ESP) from students’ perspectives. The study investigates how students perceive AI’s role in enhancing their learning experiences, particularly in terms of content quality, engagement, and learning outcomes. A qualitative approach was employed, using in-depth interviews to gather insights into students’ experiences with AI-assisted ESP learning. The findings highlight both the benefits and limitations of AI integration—namely, its capacity to personalize content and provide real-time feedback, as well as concerns around accuracy and over-reliance on technology. This article contributes to the growing discourse on AI in education by offering a nuanced understanding of students’ interactions with AI-driven tools. The results provide practical implications for educators, policymakers, and developers aiming to optimize AI applications in ESP instruction. Received 15th December 2024; Revised 5th April 2025; Accepted 30th April 2025